AP1 Transcription Factors in Epidermal Differentiation and Skin Cancer - Richard L. Eckert; Gautam Adhikary; Christina A. Young; Ralph Jans; James F. Crish; Wen Xu; Ellen A. Rorke (Journal of Skin Cancer)
AP1 (jun/fos) transcription factors (c-jun, junB, junD, c-fos, FosB, Fra-1, and Fra-2) are key regulators of epidermal keratinocyte survival and differentiation and important drivers of cancer development. Understanding the role of these factors in epidermis is complicated by the fact that each protein is expressed, at different levels, in multiple cells layers in differentiating epidermis, and because AP1 transcription factors regulate competing processes (i.e., proliferation, apoptosis, and differentiation). Various in vivo genetic approaches have been used to study these proteins including targeted and conditional knockdown, overexpression, and expression of dominant-negative inactivating AP1 transcription factors in epidermis. Taken together, these studies suggest that individual AP1 transcription factors have different functions in the epidermis and in cancer development and that altering AP1 transcription factor function in the basal versus suprabasal layers differentially influences the epidermal differentiation response and disease and cancer development.